Foreign Informational Lobbying Can Enhance Tourism : Evidence from the Caribbean - Gawande, Kishore; Maloney, William; Montes-Rojas, Gabriel (2012)
There exist legal channels for informational lobbying of US policymakers by foreign principals. Foreign governments and private sector principals frequently and intensively use this institutional channel to lobby on trade and tourism issues. This paper empirically studies whether such lobbying effectively achieves its goal of trade promotion in the context of Caribbean tourism, and suggests the potential for using foreign lobbying as a vehicle for development. Panel data are used to explore and quantify the association between foreign lobbying by Caribbean principals and US tourist arrivals to Caribbean destinations. A variety of sensitivity analyses support the finding of a strong association. The policy implications are obvious and potentially important for developing countries.